2008
DOI: 10.1080/10934520802171618
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of stabilized/solidified refinery oily sludge and incinerated refinery sludge with cement using XRD, SEM and EXAFS

Abstract: Solidification/stabilization (S/S) of refinery oily sludge and incinerated oily sludge (ash) with cement type I42.5 and II42.5 was investigated using, X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM) combined with Energy Dispersive Spectroscopy (EDS) and Extended X-ray Absorption Fine Structure (EXAFS). The results showed that delayed ettringite formation (DEF) and major cement hydration reactions occurred. XRD analysis of S/S oily sludge samples revealed cement-bearing solid phases, such as portlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The sludge samples were first dried at 103 °C to remove the moisture content (Karamalidis et al 2008), and then allowed to cool at room temperature until the weight was constant. Sample pellets of 13 mm diameter were prepared for chemical element analyses using scanning electron microscopy (SEM, Hitachi S-4700) equipped with energy-dispersive spectroscopy (EDS, EDAX Genesis).…”
Section: Sludge Characterizationmentioning
confidence: 99%
“…The sludge samples were first dried at 103 °C to remove the moisture content (Karamalidis et al 2008), and then allowed to cool at room temperature until the weight was constant. Sample pellets of 13 mm diameter were prepared for chemical element analyses using scanning electron microscopy (SEM, Hitachi S-4700) equipped with energy-dispersive spectroscopy (EDS, EDAX Genesis).…”
Section: Sludge Characterizationmentioning
confidence: 99%
“…Therefore, pH of elutes was decreased and stabilization and solidification of heavy metals occurred. In addition, Iron oxide (22.52%) and Silicon dioxide (18.01%) have a positive effect on anion and metal immobilization in the solidified waste samples, because they act as sorbents, which favor surface complexation and precipitation of anions and metals on their surface (Karamalidis et al, 2010). As can be observed in Table 3, the concentration of chromium (Cr) was increased in FCC powder (0.23 ppm) compared with neat ash (<0.05 ppm).…”
Section: Cernementioning
confidence: 99%
“…Karamalidis et al [27] investigated solidification/stabilization (S/S) of refinery oily sludge and incinerated oily sludge (ash) with cement type I42.5 and II42.5 using x-ray diffraction (XRD), scanning electron microscopy (SEM) combined with energy dispersive spectroscopy (EDS) and extended x-ray absorption fine structure (EXAFS). The results showed that delayed ettringite formation (DEF) and major cement hydration reactions occurred.…”
Section: Stabilization Measuresmentioning
confidence: 99%